Yongya Manggena Mundhum: Orality, Lineage, and Yakthung Identity (Voice of History, 2025)
This study examines the lineage, oral traditions, and historical narratives of the Yongya clan through the Orality Text embedded in Manggena Mundhum. Tracing their genealogy to the Sawa Yehang Dynasty, one of the foundational lineages of Yakthung (Limbu) society, the clan bears ancestral titles such as Khambongba Sa and Lungbongba Sa [Indigenous], reflecting their socio-spiritual responsibilities. Manggena Mundhum is more than a ritual; it serves as a living historical archive and Indigenous epistemology, interweaving spirituality, memory, and identity. Transmitted orally across generations, it offers an alternative to text-based historiography and sustains collective knowledge within the community. Ritual specialists, Phedangba, Samba, Yeba, and Yema, act as spiritual guides, historians, and custodians of this ancestral wisdom. Grounded in an Indigenous research paradigm, the study embraces relational ways of knowing, oral tradition, and ancestral memory as valid methodologies rooted in spiritual continuity and lived experience. Using qualitative methods informed by Indigenous methodology, including oral history documentation, participant observation, and ethnographic fieldwork, the research engages ritual practitioners and elders to capture embedded relational knowledge. The findings reveal a deep historical continuity between the Yongya clan and the Sawa Yehang Linease, extending back to the Neolithic era. The study challenges Eurocentric historiographical models and affirms the Mundhumic worldview as a legitimate historical and philosophical paradigm. It highlights the centrality of oral tradition in shaping Yakthung identity and cultural heritage, reinforcing the significance of Mundhum in preserving Indigenous memory and epistemology.